2021
DOI: 10.1159/000515610
|View full text |Cite
|
Sign up to set email alerts
|

Donors for SARS-CoV-2 Convalescent Plasma for a Controlled Clinical Trial: Donor Characteristics, Content and Time Course of SARS-CoV-2 Neutralizing Antibodies

Abstract: <b><i>Background:</i></b> Convalescent plasma is one of the treatment options for COVID-19 which is currently being investigated in many clinical trials. Understanding of donor and product characteristics is important for optimization of convalescent plasma. <b><i>Methods:</i></b> Patients who had recovered from CO­VID-19 were recruited as donors for COVID-19 convalescent plasma (CCP) for a randomized clinical trial of CCP for treatment of severe COVID-19 (CAPSID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 31 publications
4
30
0
5
Order By: Relevance
“…A total of 116 vaccinated individuals had no history of COVID-19; 28 were COVID-19-convalescent and analyzed separately. A total of 162 unvaccinated COVID-19-convalescent individuals served as a reference cohort [ 5 , 6 , 7 ], for which the day of positive pharyngeal swab nucleic acid amplification test (NAT) was considered as timepoint 0. Using identical platforms, we compared the different vaccination cohorts side-by-side, among one another as well as against the reference cohort (cohort I).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 116 vaccinated individuals had no history of COVID-19; 28 were COVID-19-convalescent and analyzed separately. A total of 162 unvaccinated COVID-19-convalescent individuals served as a reference cohort [ 5 , 6 , 7 ], for which the day of positive pharyngeal swab nucleic acid amplification test (NAT) was considered as timepoint 0. Using identical platforms, we compared the different vaccination cohorts side-by-side, among one another as well as against the reference cohort (cohort I).…”
Section: Resultsmentioning
confidence: 99%
“…A study in Mexico did not find a difference in the expression of anti-SARS-CoV-2 Abs between adult and children convalescents, neither between different COVID-19 severity groups [ 23 ]. Similarly, Körper et al reported no correlation of age with nAb levels in German CCP donors [ 22 ]. Bartleson et al suggested that different observations related to link between age and anti-SARS-CoV-2 Ab levels could be explained if one considers that Abs have two roles during viral infections—viral clearance and antibody-mediated enhancement of viral entry into the host cells [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is previously reported that comorbidities can lead to an increased level of proinflammatory cytokines which can have a stimulatory effect on humoral response [ 63 ]. Nevertheless, Körper et al did not report the link of body weight with nAbs level in CCP donors [ 22 ]. Additionally, no correlation with anti-SARS-CoV-2 Abs level was found in the persons with chronic liver disease, chronic lung disease or diabetes [ 52 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Detection of Anti-SARS-CoV-2 Antibodies tiierten Studien zur Anwendung von Rekonvaleszentenplasma für die Behandlung schwerer Verläufe von COVID-19 heraus. Auch der DRK-Blutspendedienst Baden-Württemberg -Hessen legte eine entsprechende Studie in Deutschland auf (CAPSID; Eudra-CT2020-001310-38, NCT04433910), für die bis Ende 2020 über 200 potenzielle Spender*innen gescreent und letztlich 319 Rekonvaleszentenplasmen von 144 Spender*innen gewonnen werden konnten [6]. Für die Testung eines Teils dieser genesenen Patient*innen wurden anfangs parallel Testplattformen verschiedener Hersteller wie Abbott, EUROIMMUN, Roche und Snibe herangezogen und mit der aufwendigen Neutralisationstestplattform des sogenannten Plaque Reduction Neutralization Test (PRNT) der Charité -Universitätsmedizin Berlin unter Verwendung von Wildtyp-SARS-CoV-2 verglichen [7,8].…”
Section: Nachweis Von Antikörpern Gegen Sars-cov-2unclassified